The soluble HFE isoform – a regulator of iron absorption in the duodenum - Silva, Bruno (2014)
Objective: Dietary iron absorption regulation is a key-step for body iron homeostasis. Once inside the enterocyte, iron is directed to the basolateral membrane being oxidized by hephaestin, which mediates iron efflux towards circulatory transferrin in cooperation with ferroportin. Besides the HFE full-length protein, the HFE gene codes for alternative splicing transcripts responsible for the synthesis of a soluble form of HFE protein (sHFE). The main objective of this work was to assess whether sHFE plays a role in iron absorption regulation in duodenum. In particular, we intended to determine if sHFE transcript levels respond to different iron conditions in duodenal cell models. Also, we aimed to investigate the functional effect of the sHFE protein on the expression of iron metabolism-related genes in duodenal cell models as well as, in vivo, in duodenum biopsy samples. Materials and Methods: The levels of sHFE transcripts were measured in HuTu-80, Caco-2, and HT-29 cells, after holo-Tf stimulus. The expression of iron metabolism-related genes was determined after endogenous and exogenous overexpression of the sHFE protein. Moreover, expression levels of sHFE and HEPH were quantified by RT-qPCR in 6 RNA samples from duodenum biopsies of dyspepsia patients. Results: Our in vitro results have shown that the sHFE transcripts expression is up-regulated by intracellular iron. Hephaestin and duodenal cytochrome b expressions are down-regulated by endogenous sHFE protein. Exogenous sHFE stimulus also down-regulates hephaestin levels by a clathrin-independent, dynamin-mediated and RhoA-regulated endocytosis mechanism. In agreement, we found that HEPH expression negatively correlates with sHFE levels in the human duodenum. Conclusion: sHFE may be an important iron metabolism homeostasis regulator which levels vary according to intracellular iron. It controls hephaestin expression and most likely the dietary iron absorption in the duodenum.